Obesity and the Risk of Thyroid Cancer: A Literature Review - Piątkowska, Karolina; Jaroń, Aleksandra; Wiklińska, Agata; Śliwińska, Martyna; Wójtowicz, Katarzyna; Walczak, Agata; Niegowska, Wiktoria; Wirkijowski, Jakub; Gajek-Flanczewska, Wiktoria; Flanczewski, Sebastian; Woźniak, Paulina; Kidacki, Kajetan (Quality in Sport, 2024)
Introduction and aim of the study: Thyroid cancer is considered the most common endocrine malignant worldwide in recent years. Also, obesity has become a true pandemic. The correlation between the increase in cases of not only obesity but also thyroid cancer could not be explained solely by earlier and more meticulous cancer diagnoses. This study aims to review the literature on the relationship between obesity and the risk of thyroid cancer. Materials and Methods: The authors conducted a comprehensive review of the literature available in PubMed and Medline databases focusing on the terms "thyroid cancer" and "obesity". Results: Obesity is associated with a state of chronic inflammation and nonspecific activation of the immune system, leading to the production of cytokines and adipokines. These elements, through complex mechanisms, directly and indirectly promote carcinogenesis. Despite the association of excessive body weight with malignant tumor development, oncological treatment cannot rely solely on lifestyle changes and should be conducted precisely as it is for individuals with normal body weight. Another popular research topic in recent years has been circadian rhythm disorders. These disorders are confirmed to be a pro-carcinogenic factor but are also considered as an element that could accelerate diagnosis. Conclusions: Understanding the relationship between obesity and thyroid cancer, primarily molecular mechanisms is essential for developing effective preventive and therapeutic strategies to reduce the risk of thyroid cancer in obese patients.